A ruína da contemporaneidade: valorização, preservação e projeto. Uma estratégia de intervenção na Central Termoelétrica do Freixo - Nuno Luís Duarte Santiago (2015)
This dissertation proposes the development of the apparently contradictoryrelationship between 'ruin' and 'contemporaneity', exploring the subjective qualitiesof the two concepts and the possibilities of a inter-relationship or even a mutualvalorization.The theme of the values acquired by a building over time has been discussedand systematized during the last two centuries, resulting in a series of definitions andconcepts that are developed in the present dissertation.Considering the strategies proposed by the bodies responsible for preserving thearchitectural heritage of the twentieth century, and taking into account the formal andmaterial characteristics of this architecture, examples of contemporary interventionsruined monuments whose main objectives are to preserve the documentary andmaterial value are analyzed, as well as their narrative and expressive potential as amemory storage medium.For a framework of concepts and strategies studied, a proposal for interventionin the Central Termoelétrica do Freixo is presented, illustrative of the problemsassociated with the integration of the ruin in contemporary landscape, from the urbanscale to the architectural detail, with a program that simultaneously respects thecollective memory and material authenticity, and allows for the enjoyment and reuseof the building by the local communities. The work thus seeks to deepen concepts and strategies of intervention onthe contemporary ruin, from its theoretical definition to its operative application,proposing to value , preserve and project the ruin for the people and for the future.